Dynamical Metabolic Model for Optimizing Biotin-Regulated Lipid Production in Microalgae-Bacteria Symbiosis - Pessi, Bruno Assis [UNESP]; Bernard, Olivier (Elsevier, 2024)
Exploiting natural symbioses to enhance productivity of bioprocesses is an emerging trend. For optimizing such complex associations of microorganisms, a model of symbiotic interactions is vital. This challenging task has attracted much attention. Here, a reduced metabolic model describing a symbiotic interaction between bacteria E. coli, overproducing vitamin biotin (B7), and microalgae Chlorella is developed. The symbiosis involves B7 exchange, impacting lipid synthesis regulation in microalgae. Our model shows a trade-off between light availability and biotin production, leading to an optimization problem for lipid production. We numerically determine the optimal conditions, demonstrating the feasibility of this strategy to enhance microalgae cultivation.
Keywords: Bioprocess control; Metabolic engineering; Microalgae; Microbial technology; Model reduction; Optimization